Knowledge Of Dental Caries Before And After Counseling Using Board Game Media For Students At SDN Rangkah 1 Surabaya : Pengetahuan Karies Gigi Sebelum Dann Sesudah Penyuluhan Menggunakan Media Board Game Pada Siswa SDN Rangkah 1 Surabaya - Najwa Maulida Manik; Siti Fitria Ulfah Siti Fitria; Bambang Hadi Sugito (Poltekkes Kemenkes Surabaya, 2024)
The highness of dental caries score in students of SDN Rangkah 1 Surabaya is 8,4 where according to WHO, the DMF-T index above 6,6 is in the very high category. Dental caries can occur due to several factors, one of which is due to a lack of dental caries knowledge. Therefore, to increase students knowledge about caries, a board game was created to help convey information about dental caries. The purpose of the research was to find out the knowledge of dental caries of students of SDN Rangkah 1 Surabaya before and after counseling using board game media. The descriptive research method with the number of respondents was 48 students of SDN Rangkah 1 Surabaya which was counseling using board game media with data collection techniques using pretest and posttest questionnaires. The data analysis technique is by recapping the data results and then categorizing them according to the research criteria and presented in the form of tables. The results of this study are the knowledge of students of SDN Rangkah 1 Surabaya before counseling using board game media in the medium category and the knowledge of students of SDN Rangkah 1 Surabaya after counseling using board game media in the good category.